COMBINED EFFECT OF FLUSHING AND HORMONAL TREATMENT ON REPRODUCTIVE PERFORMANCE OF LOCAL GOAT. - Araz O. B.; E. Alkass; M. S. Barwary (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to investigate the combined effect of flushing and hormonal treatment on reproductive aspects of local goats, 60 adult does were divided equally into two groups, the first was fed concentrate plus grazing commencing 3 weeks prior to mating and continue for 4 weeks post mating (flushed) F, whereas the 2nd group was raised on pasture only (P). All does were synchronized using impregnated with 40 mg medroxy acetate for 14 days. Following sponges withdrawn, the flushed and non- flushed does were then sub-divided in to four equal groups, the 1st flushed does were injected with 250 i.u hCG (T1), the 2nd only flushed (T2), the 3rd was only injected with hCG (T3) and the 4th was the control (T4). Results revealed that estrus response was significantly higher in T1 (100%), followed by T3 and T4 (86.66%) and T2 (80%). Fertility rate was significantly (P˂0.01) higher in T1 (80%) followed by T3 (73.33%), T4 (66.66%) and T2 (60.0%). Highest kidding rate (120.0%) and litter size (1.50) was noticed in T1, while the lowest kidding rate (86.66%) were found in T2 and T4. Insulin level was significantly higher in flushed does (6.04) compared to non-flushed does (2.81 uIU/ML).